Functional evaluation of surgical treatment for oral and oropharyngeal tumor - Michi, Kenichi (Journal of Japanese Society of Oral Oncology, 2001)
Recently, many techniques of reconstructive surgery to correct the tissue defects after abrative surgery of oral and oropharyngeal cancer have been developed. However, their functional effects or indications are controversial because of few reports of objective examination of postoperative function. Summary of the appropriate methods to evaluate postoperative functions and functional results of oral and oropharyngeal cancers are as follows. 1. Appropriate methods to evaluate postoperative functions are as follows : Synthetical evaluation of oro-nasal separation, one hundred syllable Japanese speech intelligibility test and speech intelligibilty in conversation are good to evaluate speech function. Questionaire interview method, low-adhesive colour-developing chewing-gum method and swallowing examination using water are useful to evaluate function of ingestion. 2. Functional disorders due to surgically acquired maxillary defects are improved by maxillary prostheses usually. Placement of a speech appliance in combination with maxillary obturator prostheses or implant insertion in remaining or reconstructed maxilla are of f ctive to improve insufficient oral functions. Although overall oral functions of reconstructed and non-reconstructed cases are similar, characteristics of the disorders are different from each other. 3. Surgical reconstruction by a flexible and thin flap like a radial forearm flap and prosthetic obturator combined with speech aid appliance should be applied selectively based on the extent of resection of the soft palate. A bulky flap like a rectus abdominus myocutaneous flap is applicable to a resection of lateral wall of the oropharynx, when tissue defect exted to the deep region. The dif f ernce in postoperative oral functions between various flaps reconstructed are unclear. Combined appropriate diagnosing techniques and potimal rehabilitation program are needed to obtain eary improvement of dysphagia frequently observed after surgery. 4. The extent of the tongue and the mouth floor resected and operation site affected the oral functions. Patients resected the lateral part of the tongue and the mouth floor obtain significantly better function than patients resected anterior part of them. The cases resected less than a half of the tongue can obtain excellent oral function by a reconstruction with a flexible flap like a radial forearm flap. But, bulky flap like rectus abdominus myocutaneous flap is useful in subjects resected total or subtotal tongue. Optimal rehabilitation program are needed to improve dysphagia observed frequently in subjects resected large extent of the tongue and the mouth floor. 5. Severe functional disorders are not observed in subjects resected mandible or buccal region usually. Disorder in masticatory function significantly observed after mandibulectomy can be improved by implant insertion in bone grafts.